A case study on cryopreservation of African sheep semen for the Red Maasai, Dorper breeds and their crosses - Yamashiro, H.; Wando, J.R.; Okoth, S.; Sugimura, S.; Moisyadi, S.; Sato, E.; Rege, J.E.O.; Okeyo Mwai, Ally (2011)
The objective of this study was to examine the effect of different concentrations of trehalose and raffinose in Tris-citric acid-glucose (TCG) egg yolk extender for the sperm freezability of Red Maasai sheep, another African breed- the Dorper and their crosses. The results showed that Red Maasai, Dorper and their crosses sperm could be cryopreserved by extending with 0.075 to 0.01 M trehalose or raffinose-TCG egg yolk extender. We conclude that the cryopreservation of currently under threat Red Maasai sheep due to uncontrolled exotic breeds sperm makes it possible to establish a gene bank for the storage of animal genetic resources for endangered species, under the management of the International Livestock Research Institute for future genetic options in an uncertain world.